2020
DOI: 10.1016/j.lfs.2020.117723
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial injury and COVID-19: Possible mechanisms

Abstract: Coronavirus Disease 2019 (COVID-19) has quickly progressed to a global health emergency. Respiratory illness is the major cause of morbidity and mortality in these patients with the disease spectrum ranging from asymptomatic subclinical infection, to severe pneumonia progressing to acute respiratory distress syndrome. There is growing evidence describing pathophysiological resemblance of SARS-CoV-2 infection with other coronavirus infections such as Severe Acute Respiratory Syndrome coronavirus and Middle East… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
355
0
45

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(444 citation statements)
references
References 44 publications
8
355
0
45
Order By: Relevance
“…The persistence of visual LGE at 3-month follow-up re ecting necrosis (persistent in ammation) or scar ( brosis) might be caused by COVID-19 and needs to be elucidated further 21 . Yet, visual LGE indicated that up to 30% COVID-19 patients have irreversible myocardial injury 22,23 , which is consistent with the ndings of the previous study and can con rm one of the main mechanisms of COVID-19 induced direct myocardial injury-myocarditis [24][25][26] . In addition, the presence of LGE has been proven to be an independent predictor of all-cause mortality and cardiac mortality in myocarditis 27,28 .…”
Section: Discussionsupporting
confidence: 91%
“…The persistence of visual LGE at 3-month follow-up re ecting necrosis (persistent in ammation) or scar ( brosis) might be caused by COVID-19 and needs to be elucidated further 21 . Yet, visual LGE indicated that up to 30% COVID-19 patients have irreversible myocardial injury 22,23 , which is consistent with the ndings of the previous study and can con rm one of the main mechanisms of COVID-19 induced direct myocardial injury-myocarditis [24][25][26] . In addition, the presence of LGE has been proven to be an independent predictor of all-cause mortality and cardiac mortality in myocarditis 27,28 .…”
Section: Discussionsupporting
confidence: 91%
“…Middle East respiratory syndrome coronavirus (MERS-CoV) cases suggests that diabetes and hypertension are equally prevalent in approximately 50% of the patients while coronary heart disease are present in 30% [17]. However, the mechanisms for destabilization, and hypoxia [27][28][29]. We suggest that myocardial injury is a problem that cannot be ignored in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 90%
“…Potential mechanisms currently proposed either invoke a direct damage to myocytes as a result of systemic in ammation, myocardial interstitial brosis, interferon mediated immune response, exaggerated cytokine response by Type 1 and 2 helper T cells or the secondary effect of coronary plaque destabilization as well as the profound hypoxia these patients have as a result of the overwhelming pneumonia. 4 Furthermore, Zhou et 5 al have also demonstrated the relationship existing between COVID-19 and angiotensin-converting enzyme 2 (ACE2), which is a monocarboxypeptidase renin-angiotensinaldosterone system enzyme that metabolizes several peptides, to enter ACE2-expressing cells. ACE2 is widely expressed in the endothelium of the heart and kidneys, 6 and that might explain the prevalence of ACI and acute kidney injury among patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%